Demands of justice: the creation of a global human rights practice - Clark, Ann Marie (Cambridge University Press, 2022)
Demands of Justice draws on original interviews and archival research to show how global appeals for human rights began in the 1970s to expand the boundaries of the global neighbourhood and disseminate new arguments about humane concern and law in direct opposition to human rights violations. Turning a justice lens on human rights practice, Clark argues that human rights practice offers tools that enrich three facets of global justice: transnational expressions of simple concern, the political realization of justice through politics and law, and new but still incomplete approaches to social justice. A key case study explores the origins of Amnesty International's well-known Urgent Action alerts for individuals, as well as temporal change in the use of law in such appeals. A second case study, of Oxfam's adoption of rights language, demonstrates the spread of human rights as a primary way of expressing calls for justice in the world.